Innovation highlights - Abdullah, Firdaus; Idris, Juferi; Tawie, Rudy; Pindah, Chrisna (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2025)
"Innovation Highlights" marks the inaugural publication by ResearchNexus UiTM (ReNeU) Unit under the Research & Industrial Linkages (PJI)Division, Universiti Teknologi MARA (UiTM) Sarawak Branch. This premieredition documents and celebrates the exceptional achievements ofUiTM Sarawak’s faculties in Invention, Innovation, and Design (IID)competitions throughout the 2024/2025 academic year.